Negotiated Islamic Moral Economy in a Multicultural Market: Pasar Belauran, Central Kalimantan - Suprehaten Suprehaten; Hilyatul Aulia; Lamsia Lamsia; Hunainah Hunainah (PT. Student Rihlah Indonesia, 2026)
This study examines the negotiation of Islamic moral economy within a multicultural market setting through a case study of Pasar Belauran, Central Kalimantan. The research employed a qualitative case study approach. Non-participant observation, in-depth interviews, and documentation were used to collect data, which were analyzed using data reduction, data display, and conclusion drawing. The findings show that the market functions not only as an economic space but also as a socio-religious arena where values are expressed and negotiated. Islamic ethical principles such as ṣidq (truthfulness), aminah (trustworthiness), and ‘ada (justice), were reflected in many trading practices, although their implementation varied according to social contexts and economic pressures. Multicultural interactions between traders and customers from different ethnic and religious backgrounds were generally perceived as harmonious and cooperative. Trade also served as a form of cultural da'wah through the informal transmission of daily Islamic values. Based on these findings, the study proposes the concept of NIME, referring to the dynamic process through which Islamic ethical values are interpreted, adapted, and negotiated within interactions among market rationality, multicultural relations, and local cultural contexts.